Handbook of Nanoelectrochemistry 2015
DOI: 10.1007/978-3-319-15207-3_19-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Anodic Aluminum Oxide: Fabrication, Characterization, and Applications

Abstract: Anodic aluminum oxide (AAO) consists of parallel pores arranged in a honeycomb-like array. Since a two-step self-organized approach in anodic alumina fabrication was invented, tremendous attention was paid to this material. Structural features of anodic alumina, like pore diameter, interpore distance, and nanoporous oxide thickness, can be fully controlled by operating conditions, including type, concentration and temperature of the electrolyte, applied voltage, and duration of the anodization process. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 305 publications
0
3
0
Order By: Relevance
“…[ 4 , 5 , 6 , 7 ]. The attractiveness of the AAO template for nanofabrication results from the ability to precisely control its thickness, pore diameter ( D p ) or interpore distance ( D c ) by simple changing electrochemical parameters, such as applied voltage, temperature, anodizing time, or the electrode distance [ 8 , 9 ]. While D p can be additionally regulated (increase) by post-processing pore broadening in acidic solutions, the D c is fixed when the anodization is completed and is mainly determined by the anodization voltage.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 , 6 , 7 ]. The attractiveness of the AAO template for nanofabrication results from the ability to precisely control its thickness, pore diameter ( D p ) or interpore distance ( D c ) by simple changing electrochemical parameters, such as applied voltage, temperature, anodizing time, or the electrode distance [ 8 , 9 ]. While D p can be additionally regulated (increase) by post-processing pore broadening in acidic solutions, the D c is fixed when the anodization is completed and is mainly determined by the anodization voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of anodic alumina synthesis by electrochemical anodization of aluminum metal and the structural features of PAOX, it has become a well-known material system in the scientific community for several decades. In the mid 90s, seminal discoveries by Masuda and co-workers reported that the regularity of the pore arrangement can be optimized to almost perfect hexagonal lattices by using appropriate electrolysis conditions, specific potentials, sufficiently long anodization times, and pretexturing of the Al substrate. This has led to an enormous increase on the studies of the functional properties and applications of such porous materials with controlled pore geometry.…”
Section: Introductionmentioning
confidence: 99%
“…These membranes can be prepared using two-step anodization of aluminum in acidic electrolytes [6]. Highly-ordered alumina have been used for the nano porous pattern production and is obtained using oxalic [12], phosphoric [13] and sulfuric [14] acids, however chromic acid is rarely used because the AAO membranes are less ordered compare to those prepared by other electrolytes. With the applications of AAO, significant advances in magnetism of nanomaterials [8], energy storage [9], sensor assembly [10] and biomaterial significance [11] have been attained.…”
Section: Introductionmentioning
confidence: 99%